2019
DOI: 10.9745/ghsp-d-18-00318
|View full text |Cite
|
Sign up to set email alerts
|

Successfully Engaging Private Providers to Improve Diagnosis, Notification, and Treatment of TB and Drug-Resistant TB: The EQUIP Public-Private Model in Chennai, India

Abstract: Based on a participatory program design that addressed the self-described needs of private providers, a local NGO offered the providers access to rapid diagnostics and support for notification and patient treatment including free anti-TB drugs. The model resulted in high provider participation, contributing more than 10% of the overall TB case notifications, and an 89% treatment success rate for drug-sensitive TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 13 publications
(6 reference statements)
1
22
0
Order By: Relevance
“…This is consistent with examples from PPP in the Asia Pacific focussed on adult health where private providers had access to free essential medicines and diagnostics, access to training and supervision, and branding to align the provider with the national program and generate demand. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] This is also consistent with approaches more globally. [39] By contrast, incentives for the public sector were often less well articulated and/ or more altruistic (improved services for adolescents), but identifying these benefits were nonetheless important to ensuring enhanced partnership.…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with examples from PPP in the Asia Pacific focussed on adult health where private providers had access to free essential medicines and diagnostics, access to training and supervision, and branding to align the provider with the national program and generate demand. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] This is also consistent with approaches more globally. [39] By contrast, incentives for the public sector were often less well articulated and/ or more altruistic (improved services for adolescents), but identifying these benefits were nonetheless important to ensuring enhanced partnership.…”
Section: Discussionsupporting
confidence: 82%
“…Thomas et al [16] suggest that to facilitate effective TB notifications among solo PPs, user-friendly intervention strategies with different options can be used, especially smartphone media, such as direct telephone calls, SMS, or applications. Another study in India demonstrated that online case reporting platform improved accessibility to reporting for private providers, however remains time-consuming and require the support of an intermediary NGO to deal with the amount of required data [17].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in India alone, optimising PSE can potentially avert 8 million deaths from TB between 2019 and 2045 8. The innovative models such as Enhanced Use of Quality Drugs and Utilization of Innovative Diagnostics for TB Management in the Private Sector contribute to increased case notifications from the private sector in India 21. However, such models need to be sustained for reaching end TB strategy targets.…”
Section: Resource Gaps Of Tb Control and Treatment Interventions In Tmentioning
confidence: 99%